Nurse Educators’ Perceptions of Teaching Strategies for Promoting Student-Centered and Self-Directed Learning in Gaunteng Province, South Africa - Matlhaba, Kholofelo (STIKes Patria Husada Blitar, 2026)
Introduction: The South African Nursing Council mandates that nursing education foster students' ability to identify their own learning needs and acquire the knowledge and skills necessary for competent, independent practice. The learning environment and teaching strategies employed by nurse educators are critical in facilitating student learning and achieving academic goals. This study explored nurse educators’ perceptions of various teaching strategies used to promote student-centeredness and self-directed learning in a nursing education context. Methods: A qualitative, explorative, descriptive, and contextual design was employed. Twelve nurse educators teaching theory courses in the first to third years of a Regulation 171 nursing programme were purposively sampled. Data were collected through individual semi-structured interviews until saturation was reached. Transcribed data were analyzed using Tesch’s eight-step thematic analysis. Results: Three main themes emerged: (1) commonly used teaching strategies, (2) perceived effects of preferred strategies, and (3) factors influencing the selection and use of teaching strategies. Each theme included multiple categories and sub-categories describing the educators’ experiences. Conclusions: The findings highlight key teaching strategies and influencing factors that support student-centered and self-directed learning. Addressing identified challenges is essential to improve nursing education and enhance student outcomes.